363 Aggressive angiomyxoma of the vulva: a case report. (18th September 2019) - Plurad, KG; Gaddi, A
Abstract : Objectives: To present a case of Aggressive Angiomyxoma of the vulva in a 33 year old Gravida 2 Para 2 (2002). Methods: The patient presented with a left labial mass that recurred two years after excision was done. Contrast enhanced computed tomography (CT) of the abdomen revealed an enhancing mass within the left ischioanal fossa that extended through the pelvic floor musculature into the pelvis. The soft tissue mass is seen predominantly on the left side of the vaginal region extending inferiorly to the vulva and superiorly to the uterus at the level of L5 vertebra. The mass displaced and compressed the adjacent rectum and sigmoid colon to the right. This mass measured approximately 33cm x 10 cm x 17 cm (CC x W x AP). Debulking of the mass was carried out by abdominal and perineal approach. Results: Histopathologic studies of the mass showed small, uniform, spindle shaped cells with poorly defined, pale eosinophilic cytoplasm and vesicular nuclei in a myxoid background. This confirmed the diagnosis of aggressive angiomyxoma. Conclusions: Long-term periodic follow-up with imaging studies was advised because of its high rate of recurrence in spite of negative tumor margins after wide excision.